THE STORAGE CAPACITY OF UNDERGROUND GAS STORAGES IN THE CZECH REPUBLIC - RYBA, Jakub; BUJOK, Petr; KLEMPA, Martin (GeoScience Engineering, 2019)
Sources of natural gas are in most cases located in remote areas far from the places where the gas is utilized, i.e. especially developed industrial countries to which it is transported via pipeline. However, transit gas pipelines, which are transporting extracted gas to the consumers, have a relatively limited peak capacity, the transit supplies essentially have a stable character and are not able to cover increased seasonal or peak demands for gas in gas distribution networks. The solution of this problem is the main task for underground gas storages (UGS) that through the operative regulation maintain stability and reliability of the entire gas system. This article provides a general list of options that can increase the storage capacity of natural gas in underground gas storages and focuses on factors that influence the options of an individual UGS. Keywords: natural gas, underground gas storage (UGS), storage capacity DOI 10.35180/gse-2019-0014